Choosing the optimal target area for repeated transcranial magnetic stimulation in treating neuropathic pain in spinal cord injury patients: a comparative analysis - Jin, Lihua; Wang, Haonan; Dong, Yifei; Chen, Qian; Li, Linrong; Li, Yongmei (Frontiers in Neurology, 2024)
Objective The specific target area of repeated transcranial magnetic stimulation (rTMS) in treating neuropathic pain resulting from spinal cord injury (SCI-NP) remains uncertain. Methods Thirty-four participants with SCI-NP were allocated into three groups, namely, the motor cortex (M1, A) group, the left dorsolateral prefrontal cortex (LDLPFC, B) group, and the control (sham stimulation, C) group. The intervention was administered totally 10 times. Outcome measures assessed pre-(T0) and post-(T1)intervention, including Numerical Rating scale (NRS), anxiety (SAS), depression (SDS), sleep quality (PSQI), brief pain inventory (BPI), and impression of change. Results All outcomes in groups A and B significantly changed after intervention (p < 0.05), and the delta value (T1–T0) also significantly changed than group C (p < 0.05). The delta value of SDS in the group B was better than the group A, and the change of pain degree in the group B was moderately correlated with the change in PSQI (r = 0.575, p < 0.05). Both patients in the groups A and B showed significant impression of change about their received therapy (p < 0.05). Conclusion Both targets are effective, but LDLPFC is more effective in reducing depression in SCI-NP. Healthcare providers might select the suitable area according to the specific attributes of their patients.